Tanfiż Istirātījiyyah Majmū’ah al-Tahqīq litarqiyah al-Mahārāt al-Lugawiyyah liṭullāb al-Madrasah al-Ṡānawiyyah - Abdullah, Irhamudin (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research aims to evaluate the effectiveness of Group Investigation strategies to teach language skills to Class 7 students at Nurul Mujtahidin School. The study employs Classroom Action Research (CAR) methodology, consisting of cyclical planning, acting, observing, and reflecting processes. The research design includes multiple cycles to ensure continuous improvement and adaptation of teaching strategies. Data were collected from classroom observations, student performance assessments, and interviews with students and teachers. The data collection techniques involved direct observation, structured interviews, and analysis of student work. Data analysis was performed using qualitative and quantitative methods to provide a comprehensive understanding of the impact of Group Investigation strategies. The results indicate that these strategies significantly enhance students' language skills, engagement, and collaborative learning abilities. The study concludes that Group Investigation is effective and innovative. The results of this study are: 1) The teaching of language skills using Group Investigation strategies can develop students' enthusiasm by seeing their enthusiasm for learning and coming to school on time. 2) The teaching of language skills using Group Investigation strategies can develop student grades by looking at the number of students 15, the highest score of 100, the standard value of 75, which is included in the standard score of 15, and the overall average score of 84. Based on the results of this study, the authors suggest that principals, curriculum sections, and teachers pay more attention to the factors that encourage students to improve their Arabic language skills. And to the eighth grade to further increase their enthusiasm for learning Arabic.